Recent advances in integration of 2D materials with soft matter for multifunctional robotic materials. Issue 1 (24th September 2019) - Jing, Lin; Li, Kerui; Yang, Haitao; Chen, Po-Yen
Abstract : This Minireview highlights the pioneering advances in integration of 2D materials with soft matter for multifunctional robotic materials. Abstract : Emerging soft robots with infinite degrees of freedom are one step closer to providing better human–machine interactions than conventional hard and stiff robots, attributing to their outstanding compliance/adaptability, evenly distributed stress, and programmable actuating behaviors. Soft matter ( e.g., hydrogels and elastomers) with high mechanical stability has been usually adopted for the fabrication of soft robots. However, soft matter exhibits limited optical, electrical, thermal, and chemical properties that restrict the development of functional soft robots. An emerging approach is to develop multifunctional robotic materials that are reconfigurable and can provide diverse built-in functions, such as wide-spectrum protection, tactile sensing, remote control, and wireless communication. To realize this approach, two-dimensional (2D) materials with diverse yet unique physicochemical properties have been recently integrated with soft matter to bring in add-on functionalities for fabricated soft robots. In this Minireview, we highlight three integration approaches for the fabrication of 2D material–soft matter robotic materials: (i) heterogenous blending of 2D materials within soft matter precursors followed by in situ crosslinking/curing; (ii) bilayer integration of 2D materials with soft matter substrates; and (iii) post-stabilization of 2D material (or 2D material-templated) architectures with elastomers. The advantages and drawbacks of each approach regarding the fabrication process and resulting characteristics are discussed in detail. The reversible actuating behaviors and built-in capabilities of the as-fabricated 2D material–soft matter composites, as well as their further applications as multifunctional robotic materials are summarized. Finally, current research gaps and future directions regarding the development of multifunctional robotic materials are addressed from our perspective by considering the design principles for future untethered soft robots.